A Teachable Moment? David Hume and the Tower of Babel. Issue 2 (May 2022) - Hearn, Jonathan
Abstract : This essay reflects on the de-naming of the David Hume Tower at Edinburgh University in September 2020. It critically examines and contextualises the racist footnote written by Hume, that was the focus of calls to remove his name from the building. It argues that an opportunity was lost to ask deeper questions about the contribution of David Hume to current thought, and why we may want to commemorate historical figures, despite their flaws. In short, a 'teachable moment' was squandered in this event. I conclude by suggesting that such symbolic gestures as the de-naming of the David Hume Tower are not effective ways to oppose racism.